Avaliação da aplicação da manufatura enxuta para a indústria moveleira - Moróz, Guilherme (2009)
This research focuses on analyzing and assessing the implementation of a system of manufacturing, which comes from automobile industry, into a furniture industry. This system of production known as the Toyota Production System, also called lean manufacturing, is a system of production which aims to eliminate waste during the production chain and provides a product with higher quality, reliability and profitability. This system of production has been followed by many companies in different market segments and has gained strength, mainly by the expressive results obtained. The problem of research of the study is: what the main difficulties are, income and improvement accomplished with the deployment of lean philosophy in a furniture industry and how to deploy it without problems of continuity. The method of the search was inductive approach. In relation to the nature the research is characterized as being implemented, in relation to the problem approach as qualitative and / or quantitative, to the goals of search as descriptive and to the technical procedures as a case study. The furniture industry studied is one of the largest industries in the segment in the country being also a reference of the furniture pole in the city of São Bento do Sul in Santa Catarina. The technique for collecting data of the research is targeted at three points: questionnaire to 87 employees of the factory floor (representing 100% of employees working in the company for over 5 years), semi-structured interviews with 4 managers and review of internal documents. The results show a very significant income mainly on manufacturing productivity, and reduce inventory between processes. The employees were interested in participating in the deployment and the incomes have become outstanding even in the short and medium term.